On the identity of Rumex uliginosus and the occurrence of R. dentatus in Italy (Polygonaceae) - Iamonico, Duilio; Domina, Gianniantonio; Conti, Fabio (Phytotaxa, 2023)
The identity of the name Rumex uliginosus is investigated. This species was validly described by Giovanni Gussone from central Italy (Abruzzo region) and currently considered as synonym of R. dentatus or R. palustris. The occurrence in Italy of R. dentatus is based on an old record in NW-Sicily (Boccadifalco near Palermo) as R. uliginosus by M. Lojacono-Pojero in his Flora Sicula but, actually, it is not supported by herbarium material. This Sicilian locality was reported as the only place in which R. dentatus occurs in Italy. The study of the original material of R. uliginosus allowed to: 1) lectotypify the name (on a NAP specimen) and 2) highlight that this taxon can be ascribed to R. palustris (lectotypified in this paper on a Pitchford’s collection at LINN, from Great Britain). Therefore, we here propose to exclude R. dentatus from the flora of Italy.